The efficacy of anchored stand-alone spacers in comparison to conventional cage and plate in anterior cervical discectomy and fusion surgery: A meta-analysis of randomised controlled trials for clinical and radiological outcomes - Jake M. McDonnell; Salma Youssef; Tayler D. Ross; Harry Marland; Luke Turley; Gráinne Cunniffe; Stacey Darwish; Joseph S. Butler (Brain and Spine)
Introduction: Anterior cervical discectomy and fusion (ACDF) is commonly performed with cage and plate constructs to stabilise diseased or injured cervical segments. Despite it being a commonly performed procedure, there are notable rates of associated morbidity reported in the literature. Stand-alone spacers represent a novel form of instrumentation to conventional cage and plate constructs. Research question: Do stand-alone spacers have improved operative characteristics and postoperative outcomes in ACDF cohorts when compared to cage and plate constructs? Methods: A systematic review and meta-analysis was conducted of PubMed/Medline, Embase and Google Scholar databases per the Preferred Reporting Items for Systematic Reviews and Meta-Analyzes guidelines. Studies of interest included cage and plate instrumentation versus anchored stand-alone spacers for patients undergoing ACDF. Pre- and post-operative clinical and radiological outcomes were collated and compared for significance between cohorts. Results: 10 RCTs were identified and included with 779 patients total. Mean age of the entire cohort was 50.1 years. 62% (483/779) of the cohort were male. 384 patients underwent ACDF with stand-alone cage, while 395 had ACDF with conventional cage and plate. Stand-alone spacers significantly outperformed conventional instrumentation in terms of estimated blood loss (p < 0.01), total postoperative complications (p < 0.01), dysphagia rates (p = 0.04) and adjacent segment disease (p = 0.04). Non-inferiority was evident in both patient reported outcome measures and radiological outcomes. Conclusion: This meta-analysis highlights the efficacy of stand-alone spacers for the management of primarily cervical spondylitic disease for both single-level and multi-level pathology, and thus presents an attractive alternative to conventional instrumentation for patients undergoing ACDF surgery.